Tailing cDNAs with terminal deoxynucleotidyl transferase in RT-PCR assays to identify ribozyme cleavage products. - Albuquerque-Silva, J (1998)
Polytailing a cDNA with terminal deoxynucleotidyltransferase (TdT) results in the addition of a homopolymeric sequence at its 3'-end. Here we describe the use of tailing in competitive RT-PCR assays to evaluate cleavage efficiency of ribozymes. Using a system that perfectly mimics intracellular cleavage, we were able to detect as few as 1% of cleaved moieties. Furthermore, employing primers overlapping the junction between tails and the cleaved RNA moiety in non-competitive assays, the sensitivity of the method could be improved to <10 fg. Using the latter protocol and reactions employing a trans -acting hairpin ribozyme targeting the nucleocapsid mRNA of the mumps virus, we were able to demonstrate ribozyme-induced cleavage.